2020
DOI: 10.9734/aprj/2020/v5i130099
|View full text |Cite
|
Sign up to set email alerts
|

Clay Pot Irrigation- A Review Study

Abstract: Water is the primary input for crop production and increasingly becomes scarce due to its high demand in agricultural sector. Quality of water is assuming great importance with the increasing demand in industries, agriculture and rise in standard of living. Agriculture is the major user (89%) of India’s water resources. However, dwindling of freshwater resources and deterioration of irrigation water quality due to its overuse to meet up the high demands in agriculture sector becomes the serious concern in sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The pottery irrigation can provide water to plants and result in a large number of fruits. This is in line with Adhikary and Pal (2020), which reported that clay pot irrigation improves soil physical properties, soil organic carbon, and water use efficiency. In addition, the nutrient content of soils influences the growth and development of plants, and adequate nutrients are needed in plant leaf control.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The pottery irrigation can provide water to plants and result in a large number of fruits. This is in line with Adhikary and Pal (2020), which reported that clay pot irrigation improves soil physical properties, soil organic carbon, and water use efficiency. In addition, the nutrient content of soils influences the growth and development of plants, and adequate nutrients are needed in plant leaf control.…”
Section: Discussionsupporting
confidence: 92%
“…The basic concept underlying drip irrigation is to keep a bulb of moist soil, thus, roots can absorb water adequately (Wang et al, 2011). Clay pot irrigation can improve soil structure by enhancing the efficiency of plant water use and soil organic carbon and improving soil fertility (Adhikary & Pal, 2020). However, the pottery irrigation has various effects on the irrigated soil, and crop yield depends on the size of the pot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of the irrigation system proposed in this work compared to the traditional systems is the simplicity of the manufacturing with the absence of assembled parts. Furthermore, it is possible to adapt the porosity of the permeable structure according to the water permeability of the soil and the needs of the plant to be irrigated [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%